A novel BLK-induced tumor model - David Leander Petersen; Jens Berthelsen; Andreas Willerslev-Olsen; Simon Fredholm; Sally Dabelsteen; Charlotte Menné Bonefeld; Carsten Geisler; Anders Woetmann (Tumor Biology, 2017)
B-lymphoid tyrosine kinase (BLK) is a non-receptor tyrosine kinase belonging to the SRC family kinases. BLK is known to be functionally involved in B-cell receptor signaling and B-cell development. New evidence suggests that B-lymphoid tyrosine kinase is ectopically expressed and is a putative oncogene in cutaneous T-cell lymphoma and other T-cell malignancies. However, little is known about the role of BLK in lymphomagenesis, and the oncogenic function seems to depend on the cellular context. Importantly, BLK is also ectopically expressed in other hematological and multiple non-hematological malignancies including breast, kidney, and lung cancers, suggesting that BLK could be a new potential target for therapy. Here, we studied the oncogenic potential of human BLK. We found that engrafted Ba/F3 cells stably expressing constitutive active human BLK formed tumors in mice, whereas neither Ba/F3 cells expressing wild type BLK nor non-transfected Ba/F3 cells did. Inhibition of BLK with the clinical grade and broadly reacting SRC family kinase inhibitor dasatinib inhibited growth of BLK–induced tumors. In conclusion, our study provides evidence that human BLK is a true proto-oncogene capable of inducing tumors, and we demonstrate a novel BLK activity–dependent tumor model suitable for studies of BLK–driven lymphomagenesis and screening of novel BLK inhibitors in vivo.